2017
DOI: 10.1039/c7ra90019h
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Single-crystal TiO2 nanowires by seed assisted thermal oxidation of Ti foil: synthesis and photocatalytic properties

Abstract: Correction for ‘Single-crystal TiO2 nanowires by seed assisted thermal oxidation of Ti foil: synthesis and photocatalytic properties’ by E. Arcadipane et al., RSC Adv., 2016, 6, 55490–55498.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the contrary, dense, long, and thin NWs were formed when the oxidation temperature was increased to 700 °C (Figure 4c). Early studies demonstrate that the Ti diffusion temperature required to form nanowires is above 800 °C (in Ti foils) [20,32]. Nevertheless, we observed that this temperature decreases to 650 °C in the presence of Au nanoparticles.…”
Section: Morphological and Structural Characterizationmentioning
confidence: 47%
See 3 more Smart Citations
“…On the contrary, dense, long, and thin NWs were formed when the oxidation temperature was increased to 700 °C (Figure 4c). Early studies demonstrate that the Ti diffusion temperature required to form nanowires is above 800 °C (in Ti foils) [20,32]. Nevertheless, we observed that this temperature decreases to 650 °C in the presence of Au nanoparticles.…”
Section: Morphological and Structural Characterizationmentioning
confidence: 47%
“…This base can be clearly observed when the oxidation time is longer than 3 h. Figure 7 shows that few NWs cause a change of direction with very sharp edges. This is due to the extended defects in the crystallographic structure of the NWs [32]. These defects can lead to an abrupt change of crystal structure orientation in NWs, which results in a sharp change of the main growth direction.…”
Section: Growth Mechanismmentioning
confidence: 99%
See 2 more Smart Citations